Aesthetic Analysis Of Artworks Created Using Artificial Intelligence (Eurasian Research Bulletin, 2025)
This article examines the aesthetic analysis of artworks created using artificial intelligence (AI). AI has recently entered the process of art creation and gained significant importance. The paper analyzes the aesthetic and technical features of AI-generated artworks compared to human-made art.]